Gold nanoparticles decorated multilayer mxene: towards highly selective and sensitive gas sensor at room temperature - Pu Shi; Zhikun Wang; Fan Shi (Materials Research Express)
The catalytic properties of noble metal nanoparticles can enhance the adsorption capacity of sensors for target gases when compounded with MXene. In this study, a nanocomposite of gold nanoparticles (Au NPs) and MXene was prepared using a simple self-reduction process, and its microstructure, electrochemical valence states, specific surface area, and other properties were characterized. Gas sensitivity tests conducted on the Au@MXene-20 sensor revealed excellent selectivity for NH _3 at room temperature. The response value to 100 ppm NH _3 at room temperature was 15.1%, approximately three times that of pure MXene, with response and recovery times of 118 s and 219 s, respectively. Moreover, the composite sensor exhibited a low detection limit, demonstrating a response of 3.496% to 5 ppm NH _3 at room temperature. Additionally, the Au@MXene-20 sensor possessed good repeatability, long-term stability, and moisture resistance. Therefore, the Au@MXene-20 sensor studied and prepared in this paper has been proven to be well-suited for NH _3 detection in harsh environments.